Supporting Team Reflexivity During the COVID-19 Lockdown: A Qualitative Study of Multi-Vision Groups In-person and Online - Parrello, Santa; Fenizia, Elisabetta; Gentile, Rosa; Iorio, Ilaria; Sartini, Clara; Sommantico, Massimiliano (Frontiers in Psychology, 2021)
Introduction The professional self is often hindered by a lack of self-care and poor work-life balance, and cannot be considered an unlimited resource. Given this, the reflexive team is an important organizational tool for protecting workers’ well-being. The non-profit organization Maestri di Strada (MdS) (“Street Teachers”) conducts action research in the area of socio-education. The main tool used by the group to protect the well-being of its members is a guided reflexivity group, inspired by the Balint Group and termed the Multi-Vision Group (MG). In March 2020, because of the COVID-19 lockdown, the MdS team had to quickly revamp its working model, and MGs were held online for the first time. Aim Through qualitative research that takes a longitudinal approach, the aim of this study is to evaluate the efficacy of the MG in supporting the team’s reflexivity in this new online format. Method This article considers MGs during two different time periods: pre-pandemic (T1) and early pandemic (T2). During T1, the MdS team met 18 times in person, while during T2 the team met 12 times through an online platform (always under the guidance of a psychotherapist). During all sessions in both time periods, a silent observer was present in the meetings, and they subsequently compiled narrative reports. The textual corpora of the reports were submitted for a Thematic Analysis of Elementary Contexts through T-Lab Plus, in order to examine the main content of the groups’ discourse. Results The results (5 clusters in T1; and 5 in T2) show that, during T2, the group devoted considerable time to experiences tied to the pandemic (T21: schools facing the pandemic crisis; T2.2: the pandemic: death, inner worlds, and thought resistance; T2.3: kids’ stories involving physical distancing and emotional proximity). The group also came up with innovative educational initiatives that defied the lockdown (T2.4: fieldwork: the delivery of “packages of food for thought”; T2.5: the MdS group: identity and separation). Based on these findings, the MG most likely contributed to the emergence of MdS as a “resilient community”, capable of absorbing the shock of the pandemic and realizing a fast recovery response.